2021
DOI: 10.1039/d0ra08543j
|View full text |Cite
|
Sign up to set email alerts
|

Crystal polymorphism of 8OCB liquid crystal consisting of strongly polar rod-like molecules

Abstract: The studies on crystal polymorphism of 8OCB liquid crystal showing a metastable PP phase and a heterogeneous CP phase as the stable ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The obtained temperature of each transition, T 0 m , for these peaks is, respectively, at 55.62 ± 0.00 °C, 66.96 ± 0.00 °C, and 80.16 ± 0.00 °C which could be attributed to the transitions ΔH/J g −1 216.5 [25] 215.73 ± 0.01 213.99 ± 0.01 T 0 m /°C 69.3 [26] 70.57 ± 0.00 70.48 ± 0.00 α/K −1 NA 0.82 ± 0.00 0.81 ± 0.00 β/K −2 6.08 ± 0.07 7.05 ± 0.08 ΔC p,m /W g −1 K −1 − 0.02 ± 0.00 − 0.02 ± 0.00 from crystalline to Smectic-A phase (K-SmA) at 53.54 °C, Smectic-A to Nematic (SmA-N) at 65.25 °C, and Nematic to isotropic (N-I) at 78.53 °C, respectively (Table 6). The enthalpy change of these transitions was obtained from the DSC N (T), which was in good agreement with the values reported in the literature [27][28][29]. The difference in the obtained enthalpy change and the reported values is due to different calibration approaches, setting peak value instead of the onset value.…”
Section: Phase Transitions In a Liquid Crystal Compoundsupporting
confidence: 87%
“…The obtained temperature of each transition, T 0 m , for these peaks is, respectively, at 55.62 ± 0.00 °C, 66.96 ± 0.00 °C, and 80.16 ± 0.00 °C which could be attributed to the transitions ΔH/J g −1 216.5 [25] 215.73 ± 0.01 213.99 ± 0.01 T 0 m /°C 69.3 [26] 70.57 ± 0.00 70.48 ± 0.00 α/K −1 NA 0.82 ± 0.00 0.81 ± 0.00 β/K −2 6.08 ± 0.07 7.05 ± 0.08 ΔC p,m /W g −1 K −1 − 0.02 ± 0.00 − 0.02 ± 0.00 from crystalline to Smectic-A phase (K-SmA) at 53.54 °C, Smectic-A to Nematic (SmA-N) at 65.25 °C, and Nematic to isotropic (N-I) at 78.53 °C, respectively (Table 6). The enthalpy change of these transitions was obtained from the DSC N (T), which was in good agreement with the values reported in the literature [27][28][29]. The difference in the obtained enthalpy change and the reported values is due to different calibration approaches, setting peak value instead of the onset value.…”
Section: Phase Transitions In a Liquid Crystal Compoundsupporting
confidence: 87%
“…S5 in the Supplementary Material ). Thus the amorphous component after softening gradually transforms to the crystallites and smectic phase on heating which accounts for the observed increase in dielectric constant with increasing temperature before complete melting of the sample to the smectic phase at 327.6 K [32].…”
Section: Resultsmentioning
confidence: 79%
“…3a) of banded spherulite is identical to that of the commercial powder or CP crystal phase of 8OCB. We have recently shown that the CP crystal phase is composed of fibrillar nano crystallites of the compound embedded in its own amorphous solid state [32]. All the peaks observed in the XRD profile are associated with the monoclinic crystal structure of the nano crystallites.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations